2013
DOI: 10.5897/ajmr2013.6442
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of Trichoderma viride and Trichoderma harzianum against Fusarium oxysporum f sp. ciceris causing wilt of chickpea

Abstract: Fusarium wilt (Fusarium oxysporum f. sp., ciceri) is one of the major yield limiting factors of chickpea (Cicer arietinum). For eco-friendly and sustainable management of the disease, two species of antagonists (Trichoderma viride and Trichoderma harzianum) and chemical fungicide (Carbendazim 50 WP) alone or in combination with farm yard manure (FYM) were evaluated against the pathogen. The study was carried out under laboratory and field conditions. In vitro results showed that T. viride and T. harzianum alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The same condition in chili plants has been reported by [20] where the parameters of plant height and stem diameter of chili plants are not affected by the application of Trichoderma. Regarding of the ability of Trichoderma as a growth promoter, it was also reported by [21] on wheat and beans [22]. Other research showed that seed treatment methods with Trichoderma increased the plant height, the leaf area index, extensive root, net assimilation rate (NAR), plant growth rate (PGR) on shallot [23].…”
Section: Plant Growthmentioning
confidence: 79%
“…The same condition in chili plants has been reported by [20] where the parameters of plant height and stem diameter of chili plants are not affected by the application of Trichoderma. Regarding of the ability of Trichoderma as a growth promoter, it was also reported by [21] on wheat and beans [22]. Other research showed that seed treatment methods with Trichoderma increased the plant height, the leaf area index, extensive root, net assimilation rate (NAR), plant growth rate (PGR) on shallot [23].…”
Section: Plant Growthmentioning
confidence: 79%
“…Their results showed significant inhibition of mycelial growth for all bioagents tested, with T. viride and T. harzianum showing the maximum inhibition rates of 76.25 and 68.75% at 144 h, respectively. Interestingly, Dar et al (2013) highlighted the synergistic effect of combining T. harzianum and T. viride, resulting in a robust 87.33% growth inhibition of Fusarium mycelium. In addition, the individual application of this Trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%
“…So, several researchers searching new eco-friendly non-hazardous ideas for the management of Fusarium wilt of chick pea. In this respect a novel comprehensive sustainable approach for disease management is appreciable" [13][14][15]. The use of bioagent found to be an effective measure to manage wilt disease of chickpea.…”
Section: Introductionmentioning
confidence: 99%